Pleurocarpous mosses of Bangladesh: Family Thuidiaceae and Brachytheciaceae (Bangladesh Journal of Plant Taxonomy, 2005)
A taxonomic account of six species of pleurocarpous mosses of Bangladesh under the order Hypnobryales is given. Detailed taxonomic descriptions, illustrations, and distributions of these six species are provided. Key words Pleurocarpous mosses, Thuidiaceae, Brachytheciaceae, Hypnobryales, Bangladesh. DOI: 10.3329/bjpt.v12i2.604 Bangladesh J. Plant Taxon. 12(2): 71-84, 2005 (December)